IMPACT OF DIABETES MELLITUS AS A COMORBIDITY OF COVID-19 PATIENTS TREATED AT PANTI NIRMALA MALANG: REVIEWED FROM COAGULATION PARAMETERS - Winarko Luminturahardjo; Hustorio Aliongko Simamora; Evan Kurniawan Gianto (JURNAL WIDYA MEDIKA, 2022)
Background: Treatment of COVID-19 patients with comorbid like diabetes mellitus as more consequences such as greater mortality risk and prolonged hospitalization. One of the reasons is caused by a hypercoagulable state. Aim: To prove the difference in coagulation parameters of platelet count, C-Reactive Protein, and D-dimer between Covid-19 patients with diabetes comorbidity and without diabetes, and to analyze the correlation between coagulation parameters with the stage of pneumonia caused by Covid19. Methods: The design is a cross-sectional study. The sample was collected from patients registered whose hospitalized in an isolation ward at Panti Nirmala Hospital Malang from April to October 2021. Coagulation parameters (platelet counts, C-reactive protein (CRP), and D-dimer level) were measured from 134 patients, divided between 40 patients with diabetes mellitus and 94 patients without diabetes mellitus. Statistical analysis was performed by software SPSS 24, the version year 2016. Results: Among 134 COVID-19 patients who had diabetes and no diabetes comorbidity, there are results: no significant difference in average platelet counts between the two groups (p=0.763), and the difference in C-reactive protein is significant between the two groups (p=0.076), and the difference of D-dimer level is not significant between them (p=0.593). There is a positive correlation between CRP and D-dimer level with the stage of COVID19 pneumonia (r=0.000 and r=0.134), and on the other hand, there is a negative correlation between platelet counts with the stage of pneumonia (r=-0.126). Conclusion: COVID-19 patients hospitalized with diabetes mellitus tend to have more severe conditions marked by a higher level of coagulation parameters and correlate with the severity of pneumonia.